2004
DOI: 10.1258/0268355042555028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of chronic venous insufficiency of the leg with micronized purified flavonoid fraction in the primary care setting of India

Abstract: Objective: This study investigates whether micronized purified flavonoid fraction (MPFF) is effective and acceptable without compression or surgical intervention for the management of chronic venous insufficiency of the leg (CVIL) in the primary care setting of a tropical country such as India. Methods: A prospective observational study on patients with early CVIL drawn from the clinical practice of randomly selected physicians distributed across India. Patients received MPFF 1000 mg/day for six months withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…The professions requiring long -lasting passive static load may be considered a significant risk factor for HVI. The duration of the symptoms of the patients included in our study varied (3 to 38 years), which is also consistent with other studies 9 . Similarly, HVI is more frequent among patients with a positive family history 2,5,11 .…”
Section: The Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The professions requiring long -lasting passive static load may be considered a significant risk factor for HVI. The duration of the symptoms of the patients included in our study varied (3 to 38 years), which is also consistent with other studies 9 . Similarly, HVI is more frequent among patients with a positive family history 2,5,11 .…”
Section: The Resultssupporting
confidence: 92%
“…Pinjala et al 9 reported that purified flavonoid fraction administered for 6 months to 308 patients with HVI resulted in regression of CEAP stage (53.9%), did not change CEAP stage but decreased the symptoms (29.5%), did not change CEAP but resulted in a deterioration of the symptoms (8.1%), and finally resulted in a progression of CEAP stage (8.5%). The results of this study show that semi synthetic diosmin significantly improves CEAP classification of HVI for patients treated for a month (Table 4, Graph 3), which is more beneficial compared with the research of purified flavonoid fraction 9 . It was also demonstrated that semi synthetic diosmin decreased the capillary filtration rate for patients with HVI, with consequent reduction of oedema and clinical improvement 12 .…”
Section: The Resultsmentioning
confidence: 99%
“…1) [9]. • In a prospective observational study of six months (No. of patients = 308) involving 11 major cities of India, it was found that CVD was more prevalent at the age of 42.9 ±11.5 years [10]. • Chronic venous disease tends to affect women more than men.…”
Section: The Epidemiology: Indian Perspectivementioning
confidence: 99%
“…The prevalence of CVD in India is estimated at 42.4% in males and 57.6% in females (Fig. 2) [10]. • The most common symptoms at the time of presentation in CVI patients were lower limb pain, swelling, heaviness, and cramps.…”
Section: The Epidemiology: Indian Perspectivementioning
confidence: 99%
See 1 more Smart Citation